Community Case Study: Stack Up’s Overwatch Program, an Online Suicide Prevention and Peer Support Program for Video Gamers - Colder Carras, Michelle; Bergendahl, Mathew; Labrique, Alain B. (Frontiers in Psychology, 2021)
Traditional mental health services are often not enough to meet the needs of people at risk for suicide, especially in populations where help-seeking is stigmatized. Stack Up, a nonprofit veteran organization whose goal is to use video games to bring veterans together, recognized a need in its gaming-focused online community and created the Overwatch Program. This suicide prevention and crisis intervention program is delivered entirely through the Internet by trained community members through Discord text and voice chat. By combining aspects of virtual gaming communities, veteran mental health and community-based peer support, this program provides an innovative format for implementing crisis intervention and mental health support programs. We describe here the context and features of the program, an ongoing evaluation project, and lessons learned.